Socio-cultural proximity, daily life and shopping tourism in the Dutch–German border region - Szytniewski, Bianca; Spierings, Bas; Velde, Martin van der (Tourism Geographies, 2016)
Abstract: „This paper analyses feelings of socio-cultural proximity and distance with a specific focus on the tourist experience in cross-border shopping and everyday life practices in border regions. We examined shopping practices of Dutch border crossers who visit the German town Kleve in the Dutch–German border region. This particular border context has allowed us not only to reflect on a multidimensional approach towards socio-cultural proximity and distance, but also to examine how these different dimensions express themselves in the tourist experience when it comes to people and places that are geographically ‘close’ but assumingly socially and culturally ‘distant’ from home. Although some differences prompted feelings of discomfort, in particular, differences in social engagement, feelings of comfort stand out in our analysis of cross-border shopping tourism. Furthermore, our study shows that shopping tourism and exoticism, on the one hand, and everyday routines and the mundane, on the other hand, are closely intertwined in the lives of people living in a border region, resulting in a fluid interpretation of the exotic and the mundane in the cross-border context.“
Keywords: Einkaufen; Grenzgebiet; Kleve (Kreis Kleve); Mobilität; Sozialraum; Tourismus; Verbrauch

Elastic Migration. The Case of Dutch Short-Distance Transmigrants in Belgian and German Borderlands - Houtum, Henk van; Gielis, Ruben (Tijdschrift voor Economische en Sociale Geografie, 2006)
Abstract: „Along the Dutch-Belgian and Dutch-German border a new and interesting kind of transmigration is developing, that is migration over only a few kilometres across the border. The main characteristic of these Dutch short-distance transmigrants is that they have their houses in Belgium/Germany, but their social and working life still takes place in the Netherlands. Their transmigration is hence very elastic. This elasticity invokes the interesting question: what kind of (trans)national identity these Dutch are displaying and to what extent the Dutch desire to be and/or are socially provoked to be integrated in the neighbouring Belgian/German society. These cross-border spaces in which the short-distance migrants have their residences could very well be interesting micro-scale laboratories of the future of the nation-state in the European Union.“
Keywords: Grenzarbeitnehmer; Mobilität; Sozialraum; Wohnungsmarkt

Spheres of Transnationalism within the European Union. On Open Doors, Thresholds and Drawbridges along the Dutch–German Border - Strüver, Anke (Journal of Ethnic and Migration Studies, 2005)
Abstract: „This article addresses the European Union's claim to establish transnational spaces through co-operation across its internal borders. Focusing on the Dutch–German borderland as an example, people's practices towards this border and their perceptions of it are introduced. It is underscored that these practices are influenced by popular representations, which (re)produce bounded spaces and the barrier effect of the border, thus making it difficult to imagine a transnational space. This observation is complemented by the phenomenon that—due to a housing shortage in the Netherlands—Dutch people have recently begun to move to German places directly on the border, although they maintain their jobs in the Netherlands. Concentrating specifically on one of these German villages, Kranenburg, the emergence of a community of transmigrants is highlighted in order to reflect upon the question of whether this form of frequent short-distance border crossing fosters a European transnational sphere.“
Keywords: Europäische Integration; Grenzarbeitnehmer; Grenzgebiet; Kranenburg (Kleve); Sozialraum; Transnationalisierung